(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2012)
Recently, the Government of India ordered suspension of clinical trials on tribal girl students carried out by a non-governmental organisation, for a pharmaceutical company for HPV (human papilloma virus) virus to prevent cervical cancer. The final report of the committee appointed by the Government of India to enquire into alleged irregularities found enough evidence to suggest that there were large-scale ethical violations during the conduct of “post-licensure observational study.” In August 2010, Health and Family Welfare Minister, Government of India stated that the number of incidents involving clinical trials is increasing. Upsurge in the incidents involving clinical trials and medical research evidently points to the ineptness of the ethical and statutory provisions that are currently available in India.None of the issues concerning newer therapeutic measures and medical research except the organ transplantation have evoked a widespread public anxiety in India. Had there been public debates on medical research and clinical trials, it would have led to an energetic and prompt governmental response in the seform of rules and regulations. The need of the hour is transparency and accountability in conducting medical research and clinical trials. To achieve this, there should be a reappraisal of the ethical and legal policies concerning medical research and clinical trials which take into account the safety of the human volunteers and the establishment of a statutory authority with adequate powers to monitor and supervise the medical research and clinical trials.